Oxford international secondary science workbook grade 8 - Fullick, Ann (Karachi: Oxford University Press., 2024)
Oxford International Secondary Science Workbook for Grade 8 is a supplementary resource designed to reinforce the concepts presented in the main textbook. This workbook includes a wide range of exercises, practical activities, and review questions that encourage students to apply their knowledge across biology, chemistry, physics, and Earth sciences. With a focus on hands-on experiments and real-world applications, students are guided to deepen their understanding of scientific principles and develop critical thinking skills. The structured activities promote independent learning and collaboration, making this workbook an essential tool for solidifying knowledge and preparing students for advanced scientific studies.